Customer Loyalty during COVID-19 Outbreak: The Mediation of Customer Satisfaction in Islamic Bank - Asma' Munifatussa'idah (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
This Study aims to analyze the influence factors of customer loyalty, especially group of saving customers and single customer in Islamic commercial bank, using variable of price, relationship marketing, and customer value with customer satisfaction as an intervening variable. The study is quantitative analytical methods and presents primary data collected through questionnaire with the purposive sampling technique. Total sample of 244 respondents from all local Islamic commercial bank in Indonesia during the COVID-19 outbreak period. The analysis model is Structural Equation Model (SEM), using confirmatory factor analysis and regression weight. Then, the result of this study showed that variable price, relationship marketing, and customer value partially have a positive and significant effect toward customer satisfaction. And customer satisfaction has a significant effect toward customer loyalty in Islamic commercial bank.       Keywords: Customer Satisfaction, Customer Loyalty, Islamic Bank, COVID-19 Penelitian ini bertujuan untuk menganalisis faktor-faktor yang mempengaruhi loyalitas nasabah, khususnya pada nasabah simpanan/tabungan dan nasabah tunggal pada Bank Umum Syariah, dengan variabel harga, relationship marketing, dan nilai nasabah dengan kepuasan nasabah sebagai variabel intervening. Penelitian ini menggunakan metode analisis kuantitatif dengan data primer yang dikumpulkan melalui kuesioner, teknik yang digunakan adalah purposive sampling. Jumlah sampel pada penelitian ini 244 responden dari seluruh Bank Umum Syariah selama periode wabah COVID-19. Model analisis menggunakan Structural Equation Model (SEM), dengan teknik analisis confirmatory factor analysis dan regression weight. Hasil penelitian ini, menunjukkan bahwa harga, relationship marketing, dan nilai nasabah secara parsial berpengaruh positif dan signifikan terhadap kepuasan nasabah. Dan kepuasan nasabah berpengaruh signifikan terhadap loyalitas nasabah pada Bank Umum Syariah.Kata kunci: Kepuasan Nasabah, Loyalitas Nasabah, Bank Syariah, COVID-19